An Analysis of Imperative Sentences of the Martian Movie and Their Subtitling - Muhammad Mahfudz Asrori; Hastuti Retno Kuspiyah; Ainur Rohmah (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2019)
This study concerns with the